Life of Pi : a novel - Martel, Yann. (Orlando, Fla. : Harcourt, 2001)
The son of a zookeeper, Pi Patel has an encyclopedic knowledge of animal behavior and a fervent love of stories. When Pi is sixteen, his family emigrates from India to North America aboard a Japanese cargo ship, along with their zoo animals bound for new homes. The ship sinks. Pi finds himself alone in a lifeboat, his only companions a hyena, an orangutan, a wounded zebra, and Richard Parker, a 450-pound Bengal tiger. Soon the tiger has dispatched all but Pi, whose fear, knowledge, and cunning allow him to coexist with Richard Parker for 227 days while lost at sea. When they finally reach the coast of Mexico, Richard Parker flees to the jungle, never to be seen again. The Japanese authorities who interrogate Pi refuse to believe his story and press him to tell them "the truth." After hours of coercion, Pi tells a second story, a story much less fantastical, much more conventional--but is it more true?
"A Harvest book."
Keywords: Survival after airplane accidents, shipwrecks, etc. -- Fiction; Human-animal relationships -- Fiction; Storytelling -- Fiction; Teenage boys -- Fiction; Ocean travel -- Fiction; Zoo animals -- Fiction; Orphans -- Fiction; Tigers -- Fiction; Pacific Ocean -- Fiction; Psychological fiction; Adventure fiction